Development of PBL-Based Student Worksheets to Improve Collaborative Skills on the Effect of Environmental Temperature on Body Temperature Material - Miftahul Jannah; Rida Akmala; Sabar Nurohman; Jumadi Jumadi; Zuhdan Kun Prasetyo (AL-ISHLAH: Jurnal Pendidikan, 2024)
In the context of contemporary education, learning tools are a crucial factor in facilitating adaptive, creative and student-centered learning to meet expected and desired learning outcomes and skills. This study aimed to produce PBL-based student worksheets on the effect of environmental temperature on body temperature that is suitable for in science learning activities and to find out their practicality to improve students' collaborative skills. This research and development (RD) study used the Four D model (define, design, development, and disseminate). The feasibility and practicality of student worksheets were known to four experts, six teachers, and 17 students. Testing the feasibility and practicality of PBL-based student worksheet to improve students' collaborative skills was carried out using a product feasibility questionnaire analysis with 5 aspects (content, language, presentation, graphics, and PBL components) and a product practicality questionnaire with 3 aspects (ease of use, attractiveness, and efficiency). The research results show that PBL-based student worksheets have an average total score of 138.2 with a 'very good' classification, showing positive results in terms of feasibility and practicality. So, this student worksheet can be used in science learning activities and can be used as a sufficient means to improve collaborative skills. Therefore, science teachers should adopt this PBL-based student worksheet to support their learning activities.